Avaliação do potencial da utilização da cinza da casca de arroz para mitigação de eflorescências em argamassas de revestimento - Freitas, Huálisson Thaisson de Aquino (Universidade Federal Rural do Semi-Árido, 2018)
The high production of rice in Brazil generates abundant amount of bark, that are thrown to the environment for not having an adequate deposition or use. Several studies have shown the application of rice hulls and / or grains of rice hulls (CCA) in the construction industry, being increased in mortars and concrete, as well as in bricks for the use of popular residences. Based on this idea, this work will address the use of CCA in coatings mortars, with a usual mass dash of 1: 3(cement: sand), with the purpose of analyzing its mechanical properties as: tensile strength and compressive strength; properties linked to durability such as: absorption, capillarity, porosity. Mortars were compared with curing time (28 days, 56 days, 68 days and 98 days) and cement substitution by percentages of 10% and 15% of CCA. Initially the characterization tests were carried out through the following tests: granulometry by sieving and laser granulometry, XRD, specific area, unit mass; together with data provided by manufacturers. After determining the consistency, the specimens were molded. In addition to checking the properties mentioned above, studies were carried out to test the pozzolanic activity, with emphasis on efflorescence evaluation, measuring the amount of efflorescence salt under the surface of the specimens. The results of the characterization of the materials demonstrate that they are in the standards determined by ABNT. Regarding the durability, the mortars with CCA had a lower efflorescence formation. Regarding the resistance, conventional mortars with better results than alternative mortars (10% and 15% of CCA) are pointed out. However, the percentages of variation between a conventional mortar and an alternative mortar are not so significant, which does not compromise the technical feasibility of the CCA
Keywords: cinza da casca de arroz; argamassas; durabilidade; eflorescência; rice husk ash; mortars; durability; efflorescence; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA